Analysis the Process of Observing Class IV Students in Thematic Learning in Primary Schools - Suwarni, Risda (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research describes research conducted to explore the implementation of thematic learning with a scientific approach at SD Negeri No. 112/I. The introduction explains the background of the research, highlighting the importance of thematic learning in increasing student engagement and providing meaningful learning experiences. The research method involves observation, interviews, and documentation to collect data about the learning process. The results of the research show that students are actively involved in learning activities by carrying out various activities observing, reading, listening, listening and looking. The discussion highlights the effectiveness of the thematic learning approach in facilitating holistic and authentic understanding, and shows teacher support plays an important role in the delivery of material and understanding concepts. The novelty of this research lies in the scientific approach to thematic learning, which provides a comprehensive and problem-solving oriented learning experience. The implication of this research is the need to continue to improve and develop thematic learning approaches by paying attention to the role of teachers and the application of scientific principles in the learning process. In conclusion, this research confirms that thematic learning with a scientific approach can be an effective learning model in enriching students' learning experiences and improving the quality of learning in elementary schools.